Ascending aortic size in aortic coarctation depends on aortic valve morphology: Understanding the bicuspid valve phenotype. (1st January 2018) - Frandsen, Erik L.; Burchill, Luke J.; Khan, Abigail M.; Broberg, Craig S.
Abstract: Background: In roughly half of patients with coarctation of the aorta (CoA), the aorta may be enlarged. It is uncertain whether enlargement is independent of aortic valve morphology. We sought to compare aortic size in CoA with a tricuspid valve (TAV) to those with bicuspid aortic valve (BAV). Methods: Sixty-eight CoA patients and 20 healthy controls with prior cardiac magnetic resonance (CMR) imaging were included. CMR was retrospectively reanalyzed to measure aortic root and mid-ascending aorta. The maximum aortic diameter was compared between CoA with TAV, CoA with BAV, and control groups. Results: CoA with TAV patients ( n  = 27) had smaller aortic root diameters than CoA with BAV ( n  = 41) (32 ± 4.9 vs. 37 ± 5.8 mm, p  = 0.001), despite being older (40 vs. 32 years, p  = 0.01). Similarly, TAV CoA patients had a smaller mid-ascending aortic diameter (28 ± 4.5 vs. 33 ± 6.9 mm, p  = 0.019) than BAV patients. TAV CoA was similar to controls in all metrics. Twenty-four patients (35%) with CoA had dilated aortas (> 37 mm), of which 79% had BAV. A history of hypertension did not predict larger aortic root or mid-ascending aortic dimensions. Conclusions: In patients with CoA, TAV is associated with smaller aortic size compared to those with BAV, and similar to healthy controls. Aortic size in CoA is independent of hypertension. Therefore, aortopathy associated with BAV is likely a reflection of the BAV phenotype rather than CoA or its physiologic effects. This distinction may have implications for the frequency and types of monitoring and treatment of CoA patients.